Intraseasonal changes of body composition in professional soccer players and differences according to playing positions - Michailidis, Y.; Michailidis, C.; Primpa, E.; Fatouros, I. G.; Margonis, K.; Chatzinikolaou, A.; Douroudos, I.; Draganidis, D.; Methenitis, S. (Serbian Journal of Sports Sciences, 2013)
The purpose of this study was to examine the intraseasonal variation of body composition (BC) in elite soccer players. 23 professional players participated in the study. Percentage of body fat (BF) was measured with the use of skinfolds. Measurements were taken monthly from the beginning until the end of the season. Measurement mean values were compared among 6 specific positional roles. For seasonal variations, the analyses of variances were performed to 11 time points across the season. BM in goalkeepers differed significantly from all other groups.